Job Burnout on Subjective Well-Being Among Chinese Female Doctors: The Moderating Role of Perceived Social Support - Wang, Liping; Wang, Huiping; Shao, Shuhong; Jia, Gaizhen; Xiang, Jing (Frontiers in Psychology, 2020)
All doctors face challenges and pressures that can lead to job burnout. The dual pressures of work and family make female doctors less happy and more likely to experience burnout, but few studies have focused on female doctors. In this study we explore the influence of job burnout on female clinical doctors’ subjective wellbeing and the moderating role of perceived social support. A casual comparative study design was used for this research. Three self-reporting scales (Maslach Burnout Inventory, Perceived Social Support Scale and Subjective Wellbeing Scale) were distributed to participants, who were selected through random sampling. Participants consisted of 120 female and 120 male doctors from a hospital of Yantai City. Female doctors scored significantly higher than male doctors in the emotional exhaustion dimension (p < 0.01), and female doctors’ subjective wellbeing was lower than that of male doctors (p < 0.01). The three dimensions of job burnout and subjective wellbeing exhibited significant negative correlations, and a positive relationship was found between perceived social support and subjective wellbeing in female doctors (p < 0.01). Perceived social support, especially from family, played a moderating role between emotional exhaustion and subjective wellbeing, and the moderating effect was significant (p < 0.01). A significant difference was observed between male and female doctors; female doctors experienced more emotional exhaustion and lower subjective wellbeing than male doctors. Improving perceived social support could reduce burnout and enhance subjective wellbeing.